Study on Digital Phase-Locked Loop for Grid-connected Power Electronic Device - WANG Baogui; LI Zequan; LIN Yong; LIU Bin (Kongzhi Yu Xinxi Jishu)
As the grid-connected power electronic device has been widely applied, digital phase-locked loop (PLL) is becoming a key technology of such devices. An advanced digital SRF-PLL is applied based on the synchronous rotating reference frame, and the unified mathematical model for single-phase and three-phase is constructed. The stability and dynamic performance are analyzed and then verified by simulation and experiment, which provides a reference for the real PLL application in digital phase-locked loop of grid-connected power electronic device.